Природа как ценность культуры: генезис философских идей - Михайлик, О.Г. (Культура народов Причерноморья, 2013)
Статья посвящена проблеме природы как важнейшей жизненной ценности современной
цивилизации в условиях нарастающего экологического кризиса. Для осмысления этой проблемы
предпринята попытка рассмотреть значимость природного мира для развития материальной и
духовной культуры общества, отражение этой взаимосвязи в философских идеях и концепциях ученых и
мыслителей различных исторических эпох, а также проанализировать их роль в становлении новой
ценностной парадигмы в системе «человек-природа» в контексте сегодняшней глобальной
экологической ситуации. Стаття присвячена проблемі природи як важливішій життєвій цінності сучасної цивілізації
в умовах наростаючої екологічної кризи. Для осмислення цієї проблеми здійснена спроба розглянути
значення природного світу для розвитку матеріальної та духовної культури суспільства, відображення
цього взаємозв’язку в філософських ідеях та концепціях вчених та мислителів різних історичних епох, а
також проаналізувати їх роль в становленні нової ціннісної парадигми в системі «людина-природа» в
контексті сучасної глобальної екологічної ситуації. The article deals with the nature of life as the most important values of modern civilization in the
conditions of the growing environmental crisis. In it from the theoretical standpoint of social philosophy was an
attempt to uncover the dynamics of the relationship of man to nature in diachronic, it features a modern
conditions and justify the need for the formation of a new paradigm of value in the context of global challenges
HH1 century.
To comprehend the problem discussed ideas about the value of nature in the experience and traditions of various
historical eras and their role in shaping society's values.
The article attempts to analyze the importance of the natural world for the development of the material and
spiritual culture of the scientists, who considered nature as a value and is constantly stressing the need for
careful treatment of it.
The article highlighted the person is in relationship with nature that the most significant advances in science and
technology of the mind frees man from the domination of nature and to take into account that excessive pressure
on it is not only futile, but dangerous for mankind. The article emphasizes that the problem of optimization of
human interaction with the environment is essential not only for the survival of life on Earth, but is also
important for the person, because depletion of specific cultural ties with nature, covering his spiritual life
inevitably leads to the destruction of value and meaning of human resources experience.
But today, in the minds of people is dominated by an idea of immensity of nature, do not form an idea of its value
to modern civilization for future generations.
In the article to the attention of the search for solutions to the problem of handling the consciousness of the
people, their morals, and environmental education and awareness of environmental culture articulated in the
concept of "new environmental consciousness", the "new humanism", put forward by scientists Club of Rome.
Modern ecological crisis requires a comprehensive integrative research addressed the achievement of science,
but a full understanding of the problem assumes full consideration to its philosophical and methodological
standpoint of philosophy, which is why the philosophical concepts and ideas of past thinkers about nature, its
value to the person so meaningful and relevant for the emergence of new value paradigm in the context of the
current global environment.